2008
DOI: 10.1063/1.3000560
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium calcium oxyborate piezoelectric single crystals for ultrahigh temperature (>1000 °C) applications

Abstract: ReCa 4 O ( BO 3 ) 3 oxyborate crystals (ReCOB, where Re is a rare earth element such as Gd) were grown using the Czochralski pulling technique. The crystals belong to Cm space group and the relationships of the as-grown crystal morphology with crystallographic and physical coordinates were determined. The optimum length extensional and thickness shear vibrations of GdCOB were found for (ZYl)40° and (YXt)33° cuts, with electromechanical coupling factors k32 and k26, being on the order of 17.5% and 25% and piezo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…They do not show phase transformations up to its melting point at about 1500 • C and are, therefore, promising materials for high-temperature operation. Most remarkably, those crystals exhibit very low conductivity, for example 5 × 10 −7 S/m at 800 • C [27][28][29] which is about one and three orders of magnitude lower than that for GaPO 4 and langasite, respectively. As a consequence, the loss is very low which results in resonant devices with exceptional high resonator quality factors even at 900 • C. Currently, a maximum operation temperature of 1000 • C is reported for GdCa 4 O(BO 3 ) 3 .…”
Section: High-temperature Piezoelectric Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…They do not show phase transformations up to its melting point at about 1500 • C and are, therefore, promising materials for high-temperature operation. Most remarkably, those crystals exhibit very low conductivity, for example 5 × 10 −7 S/m at 800 • C [27][28][29] which is about one and three orders of magnitude lower than that for GaPO 4 and langasite, respectively. As a consequence, the loss is very low which results in resonant devices with exceptional high resonator quality factors even at 900 • C. Currently, a maximum operation temperature of 1000 • C is reported for GdCa 4 O(BO 3 ) 3 .…”
Section: High-temperature Piezoelectric Materialsmentioning
confidence: 96%
“…As a consequence, the loss is very low which results in resonant devices with exceptional high resonator quality factors even at 900 • C. Currently, a maximum operation temperature of 1000 • C is reported for GdCa 4 O(BO 3 ) 3 . Above that the thin film platinum electrodes used here degrade strongly [28]. However, higher operation temperatures are expected.…”
Section: High-temperature Piezoelectric Materialsmentioning
confidence: 97%
“…These crystals show the merits of high melting points (1400-1700 °C) and high effective piezoelectric coefficients d eff (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) pC/N) [20][21][22][23][24][25][26]; the evaluations of the temperature dependence of dielectric, piezoelectric and electromechanical properties, however, are limited. Of particular significance is that the monoclinic rare-earth calcium oxyborate crystals (ReCa 4 O(BO 3 ) 3 , ReCOB, Re: rare earth), which have been extensively investigated for nonlinear optical applications in the last two decades [27][28][29][30][31][32][33], were reported to exhibit good piezoelectric properties and high electrical resistivity at an elevated temperature of 1000 °C, with no phase transition prior to their melting points (~1400-1520 °C) [1][2][3][34][35][36][37][38]. Table 1 summarizes the basic characteristics of various high temperature piezoelectric crystals in monoclinic, trigonal and tetragonal systems, where the monoclinic ReCOB crystals were found to exhibit relatively high melting points, as well as relatively large piezoelectric coefficients, promising high temperature piezoelectric sensor applications.…”
Section: Open Accessmentioning
confidence: 99%
“…Compared with the commercial strain gauge and optical fiber sensors, etc., piezoelectric sensors have greater potentials in realizing high temperature (>600 °C) sensing with the merits of high accuracy, fast response time and ease of integration [1][2][3][4].…”
Section: Open Accessmentioning
confidence: 99%
“…Recently, electro-elastic properties of ReCOB type crystals, including YCOB, GdCOB, NdCOB and LaCOB, have been extensively investigated. [8][9][10][11][12][13][14][15] Among these crystals, NdCOB crystals were reported to possess a relatively high surface acoustic wave (SAW) coupling factor (k 2 = 0.8%) and low linear temperature coefficient of delay (TCD) (close to zero), 16 while YCOB crystals were observed to show high stability of electromechanical properties at elevated temperatures, 14,15 and explored for high temperature accelerometer applications. [17][18][19] In previous reports, it has been revealed that the piezoelectric coefficient d 26 and electromechanical coupling factor k 26 increase with increasing rare-earth ionic radius, the relationship between crystal structure and piezoelectric properties was established, where the distortions of Re-O and Ca-O octahedra in ReCOB crystals were believed to account for the enhancement of piezoelectric coefficient d 26.…”
Section: Motivationmentioning
confidence: 99%